Application of Tofu Waste Treatment Installation to Produce Land Remediation Culture in Punge Blang Cut Banda Aceh - Darwin Darwin; Bambang Sukarno Putra; Ramayanty Bulan; Muhammad Rizal (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research paper explores an integrated solution for managing tofu waste from the SOLO Tofu Factory. By combining anaerobic digestion technology with urban organic farming, the study aims to provide a sustainable waste management model that benefits the factory and the surrounding community. Method: The study utilized mixed methods, including qualitative interviews and quantitative on-site observations. Anaerobic digestion technology was employed for waste treatment, and its effluent was analyzed for its potential as a bio-fertilizer. A sustainable urban organic farming system was developed, utilizing treated waste for cultivation. Data analysis involved qualitative thematic and quantitative measurement analysis. Practical Applications: The integrated approach offers helpful solutions. It provides the factory with an eco-friendly waste management solution, reducing pollution. The urban organic farming system promotes sustainable agriculture and remediates land, making it cultivable. This model serves as a blueprint for similar industries, fostering community development and environmental awareness. Conclusion: The research demonstrates the effectiveness of integrating anaerobic digestion and urban organic farming for tofu waste management. This approach offers practical, scalable solutions, reducing pollution, promoting sustainable agriculture, and fostering community development.